2021
DOI: 10.1155/2021/2459573
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fuzzy Delphi Method in Forecasting and Decision-Making

Abstract: The Delphi method is a process where subjective data are transformed into quasi-objective data using statistical analysis and are converged to stable points. The Delphi method was developed by the RAND Corporation at Santa Monica, California, and is widely used for long-range forecasting in management science. It is a method by which the subjective data of experts are made to converge using some statistical analyses. This article proposes a variation of the Delphi method using triangular fuzzy numbers, where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…FDM has been applied in various fields such as management sciences, business management, humanitarian logistics, human-computer interaction, health-related research, and vocational training. The fuzzy Delphi method is widely utilized in management science for long-range forecasting and decision-making processes across various industries [102]. The FDM is applied in research on user experience, augmented reality, usability, mobile applications, and online learning in human-computer interaction [99].…”
Section: Fuzzy Delphi-dematel Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FDM has been applied in various fields such as management sciences, business management, humanitarian logistics, human-computer interaction, health-related research, and vocational training. The fuzzy Delphi method is widely utilized in management science for long-range forecasting and decision-making processes across various industries [102]. The FDM is applied in research on user experience, augmented reality, usability, mobile applications, and online learning in human-computer interaction [99].…”
Section: Fuzzy Delphi-dematel Methodsmentioning
confidence: 99%
“…The process involves designing questionnaires to assess potential KPIs. Prior studies often relied on triangular [96,100,101], trapezoidal [102], and Gaussian [103] fuzzy numbers for choosing fuzzy membership functions. Witold has demonstrated that the widely employed triangle membership functions offer a direct resolution to the problems that arise in fuzzy modeling [104].…”
Section: Fuzzy Delphi Methodsmentioning
confidence: 99%
“…Dawood et al [11] developed a fuzzy Delphi method consisting of three steps: usability criteria analysis, fuzzy Delphi analysis, and usability evaluation model development. Alharbi et al [12] proposed a variant of the Delphi method using triangular fuzzy numbers with a similar communication method to experts but a different evaluation process. Salais-Fierro et al [13] established a hybrid approach combining expert judgment with demand forecasting generated from historical data for use in the automotive industry.…”
Section: Technology Assessmentmentioning
confidence: 99%
“…This matrix is a dissemblance relation decomposable into similarity relations. Using this approach, finding a nondisjunction subgroup of experts, who are favorable to studies in public opinion, is very convenient (Alharbi and El-Wahed Khalifa, 2021) (see Table 6).…”
Section: Effectiveness Of Sustainable Intangible Capital Functionsmentioning
confidence: 99%